Unplanned pregnancy: impact of the sociocultural and emotional factors of the adolescent, 2017 - Maque Ponce, Mary Luisa (2018)
The research work was aimed at analyzing the sociocultural and emotional factors that suggest the impact of an unplanned pregnancy on adolescents. With a descriptive study and a sample of 17 pregnant adolescents, a questionnaire was used with free-response questions conducted by an indepth interview to interpret the reasons why adolescents report having become pregnant without having planned it and to identify the categories of the factors linked to these reasons. The results show the emotional category expressed by the separated parents, the absence of the father figure, the death of both parents, the upbringing by a close relative and the change of their emotions of sadness for the possibility of a provoked abortion and happiness in the continuity of pregnancy. The social category indicates that adolescents start their sexual relationships without pressure. Finally, in the cultural category, adolescents had a complicated access to information on the use of contraceptive methods; similarly, they are also unaware of the importance of prenatal care, hiding the pregnancy beyond the third month. It is concluded that these factors have an impact on the unplanned pregnancy of adolescents.